2021
DOI: 10.1007/s11135-021-01129-3
|View full text |Cite|
|
Sign up to set email alerts
|

Decision support system for ranking relevant indicators for reopening strategies following COVID-19 lockdowns

Abstract: The pandemic caused by the spread of the SARS-CoV-2 virus forced governments around the world to impose lockdowns, which mostly involved restricting non-essential activities. Once the rate of infection is manageable, governments must implement strategies that reverse the negative effects of the lockdowns. A decision support system based on fuzzy theory and multi-criteria decision analysis principles is proposed to investigate the importance of a set of key indicators for post-COVID-19 reopening strategies. Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 67 publications
(102 reference statements)
0
8
0
Order By: Relevance
“…Following the lesser of two evils principle, lockdown is necessary to be used as a counterpoison when the widespread diffusion of a virus must be slowed down. In this respect, all the possible measures must be taken by officials to reduce the collateral effects of isolation (Almulhim and Barahona, 2021 ). One way to reach this goal is to explain as clearly and completely as possible what is happening, why, how long it will last, provide activities to perform during isolation, ensuring basic supplies and reinforce the sense of altruism.…”
Section: Review Of the Literaturementioning
confidence: 99%
“…Following the lesser of two evils principle, lockdown is necessary to be used as a counterpoison when the widespread diffusion of a virus must be slowed down. In this respect, all the possible measures must be taken by officials to reduce the collateral effects of isolation (Almulhim and Barahona, 2021 ). One way to reach this goal is to explain as clearly and completely as possible what is happening, why, how long it will last, provide activities to perform during isolation, ensuring basic supplies and reinforce the sense of altruism.…”
Section: Review Of the Literaturementioning
confidence: 99%
“…Recent study also showed that the implementation of the lockdown-like policy in Italy has a good impact on pandemic conditions; the policy has successfully reduced human mobility which results in a decrease in the number of infections and deaths due to COVID-19 (Panarello and Tassinari 2022 ). As a result of the successful implementation of the lockdown during the pandemic, Almulhim and Barahona ( 2022 ) made a decision support system to investigate important indicators that need to be considered in the reopening strategy.…”
Section: Literature Reviewmentioning
confidence: 99%
“…DSS is a tool used to solve decision-making problems that Decision-Makers (DMs) face through collecting, analyzing, or organizing required information. They are used by both single or group of DMs when complex or unstructured scenarios are faced to ensure robust results [29]. While the authors of [30] stated that Information Systems (IS) are a basic component of DSS which improves the decision-making process and requires a high level of human-computer interaction to support the behavioral part of the decision-making process.…”
Section: Related Workmentioning
confidence: 99%
“…The authors of [29] conducted a study in which they used fuzzy theory-based DSS to investigate re-opening strategies for post COVID-19 period. The system is examined using principles for multi-criteria decisions to decide the importance of 16 key indicators.…”
Section: Related Workmentioning
confidence: 99%